Relationship between inflation and economic growth in Vietnam (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vietnam government considers inflation adjustment as a primary goal ofpolicies planning and implementing to achieve economic stability and GDP growth.Therefore, defining the threshold in inflation-GDP growth relationship is an importanttask to propose target inflation rate precisely. This paper investigates the thresholdbetween inflation and GDP growth in Vietnam. Inflation is assumed to have anonlinear relationship with GDP growth. The results confirm the existence of thethreshold at 6 per cent inflation point, and the negative impacts on GDP growth ofhyperinflation above the threshold and too low inflation beyond the threshold. Takinginto account the total impact of inflation on GDP growth, the effects are negative.This finding suggests that Vietnam authorities should target lower inflation of 6 percent to improve GDP growth.